Adenocarcinoma in situ of the uterine cervix: Clinical practice guidelines from the Italian society of colposcopy and cervical pathology (SICPCV). (September 2019) - Ciavattini, Andrea; Giannella, Luca; Delli Carpini, Giovanni; Tsiroglou, Dimitrios; Sopracordevole, Francesco; Chiossi, Giuseppe; Di Giuseppe, Jacopo; ,
Abstract: Objective: to provide a practical tool for the evidenced-based management of adenocarcinoma in situ (AIS) of the uterine cervix, a challenging diagnosis encountered by colposcopists in their daily practice. Methods: the proposed recommendations were drafted by the Italian Society of Colposcopy and Cervical Pathology (SICPCV) based on comprehensive reviews of previous guidelines, large uncontrolled studies, metanalysis, and sytematic reviews. The quality Level and the strength of the recommendations were graded and respectively expressed in Roman numbers (I–VI) and letters (A–E). Results: Women with all subcategories of abnormal glandular cells and AIS on cervical citology should be offered colposcopy with endocervical sampling (Strength of recommendation: A). In women with cytological AIS and negative colposcopy or endocervical curettage, an excisional treatment under colposcopic guidance is recommended (Strength of recommendation: A). If immediate post-conization endocervical sampling is positive, further conization is indicated (Strength of recommendation: C). In women who desire to preserve fertility with positive cone margins, further conization should be performed (Strength of recommendation: B). If colposcopy is adequate, a cylindrical excision that includes the whole transformation zone and at least 1–1.5 cm of endocervix beyond the squamous-columnar junction should be performed (Strength of recommendation: B). If colposcopy is inadequate, it is recommended that conization includes the whole transformation zone with a depth of 20–25 mm (Strength of recommendation: B). Hysterectomy is the standard definitive treatment for AIS in women who do not wish to preserve fertility (Strength of recommendation: B). Conclusion: the proposed recommendations should enable clinicians to correctly diagnose, treat and follow AIS patients, avoiding mismanagement.